Pertunjukan Wayang Babad Nusantara: Wahana Pengajaran Nilai Kebangsaan bagi Generasi Muda - -, Sunardi; Nugroho, Sugeng; -, Kuwato (PANGGUNG, 2016)
ABSTRACTÃÂ Wayang Babad Nusantara ÃÂ represents a creation ÃÂ of a shadow puppet show whichÃÂ  used as a means of transmission ÃÂ of nationalism ÃÂ values ÃÂ towards younger ÃÂ generations. ÃÂ This type ÃÂ of show has the aspect ÃÂ of innovations ÃÂ in several ÃÂ elements ÃÂ of pakeliran, ÃÂ which are: the heroic story ÃÂ of NationalÃÂ  heroesÃ¢â¬â¢ struggle, the authentic ÃÂ puppets bas on the reinterpretation ÃÂ of the figure in the history, a new musical score, and the scene-system with the shadow puppet show structure. ÃÂ This show is interestingly ÃÂ wrapped with the story of Gajah Mada. The spirit of these figure ÃÂ serves as the good example for young ÃÂ generations ÃÂ to love their ÃÂ country. ÃÂ TheÃÂ  nationalism ÃÂ value, ÃÂ which contain ÃÂ the teaching ÃÂ of patriotism ÃÂ and allegiance can build the awareness ÃÂ of the children ÃÂ of the nation ÃÂ so that they will always ÃÂ love the land ÃÂ of Indonesia.ÃÂ Keywords: Babad shadow puppet, nationalism ÃÂ values, ÃÂ young ÃÂ generationsÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Wayang Babad Nusantara merupakan rekayasa model pertunjukan wayang yang dipergunakan sebagai wahana transmisi nilai-nilai kebangsaan bagi generasi muda. Pertunjukan wayang ini memiliki kebaruan dalam berbagai unsur pakeliran, yaitu: cerita sejarah perjuangan pahlawan bangsa, boneka wayang hasil reinterpretasi dari figur tokoh, musik komposisi baru, dan sistem pengadegan dengan struktur pertunjukan wayang. Pertunjukan wayang ini dikemas secara menarik dengan menyajikan cerita Gajah Mada. Spirit perjuangan tokoh Gajah Mada ini memberikan suri teladan bagi generasi muda untuk selalu cinta tanah air. Nilai kebangsaan yang memuat ajaran mengenai patriotisme dan nasionalisme memberikan kesadaran dan menggugah kesadaran anak bangsa untuk selalu mencintai Tanah Air Indonesia.ÃÂ Kata kunci: wayang babad, nilai kebangsaan, generasi muda